The A to I editing landscape in melanoma and its relation to clinical outcome. Issue 1 (31st December 2022) - Amweg, Austeja; Tusup, Marina; Cheng, Phil; Picardi, Ernesto; Dummer, Reinhard; Levesque, Mitchell P; French, Lars E; Guenova, Emmanuella; Läuchli, Severin; Kundig, Thomas; Mellett, Mark; Pascolo, Steve
ABSTRACT: RNA editing refers to non-transient RNA modifications that occur after transcription and prior to translation by the ribosomes. RNA editing is more widespread in cancer cells than in non-transformed cells and is associated with tumorigenesis of various cancer tissues. However, RNA editing can also generate neo-antigens that expose tumour cells to host immunosurveillance. Global RNA editing in melanoma and its relevance to clinical outcome currently remain poorly characterized. The present study compared RNA editing as well as gene expression in tumour cell lines from melanoma patients of short or long metastasis-free survival, patients relapsing or not after immuno- and targeted therapy and tumours harbouring BRAF or NRAS mutations. Overall, our results showed that NTRK gene expression can be a marker of resistance to BRAF and MEK inhibition and gives some insights of candidate genes as potential biomarkers. In addition, this study revealed an increase in Adenosine-to-Inosine editing in Alu regions and in non-repetitive regions, including the hyperediting of the MOK and DZIP3 genes in relapsed tumour samples during targeted therapy and of the ZBTB11 gene in NRAS mutated melanoma cells. Therefore, RNA editing could be a promising tool for identifying predictive markers, tumour neoantigens and targetable pathways that could help in preventing relapses during immuno- or targeted therapies.